HUBUNGAN ANTARA RIWAYAT KOMPLIKASI KEHAMILAN DENGAN GANGGUAN PERKEMBANGAN MOTORIK KASAR PADA ANAK USIA 0-36 BULAN - Yulisha Eva Oktaviani Baijery (Health Media, 2023)
Child development is a child's changes that can be seen from various aspects such as social, cognitive, and motor. Motor development is divided into two, namely gross motor and fine motor. Gross motor is an activity that involves large groups of muscles while fine motor involves only certain muscles. Children's gross motor development begins to be seen from the age of 0 months when the baby is moving his hands and movements are conscious. At this age, gross motor skills begin to form and focus. Gross motor development occurs because the maturity of the nervous system has been formed. if the maturity of the nervous system slows down or does not develop, gross motor development will be hampered. The factors that affect children's gross motor disorders are not yet known with certainty. However, pregnancy complications affect gross motor disorders. Mothers who have a history of pregnancy complications have a 30% risk of giving birth to children with impaired gross motor development compared to mothers who give birth without pregnancy complications. This research is a quantitative research with a case control research design. The results of this study obtained a p value = 0.007, which means that there is a relationship between a history of pregnancy complications and gross motor development disorders